2018
DOI: 10.3892/ol.2018.9825
|View full text |Cite
|
Sign up to set email alerts
|

Genomic amplification of HPV, h‑TERC and c‑MYC in liquid‑based cytological specimens for screening of cervical intraepithelial neoplasia and cancer

Abstract: Cervical cancer is one of the most prevalent female cancer types in developing countries. ThinPrep cytological test (TCT) and human papillomavirus (HPV) detection are canonical screening methods for cervical cancer currently. However, there are limitations to these techniques. The aim of the present study was to identify efficient and practical methods for the screening of cervical intraepithelial neoplasia (CIN) and carcinoma. Residual PreservCyt specimens were obtained from 1,000 women who were admitted betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The proportion of cases with hTERC gene overexpression showed a significant increment with progressively increasing cytological and histological abnormalities, findings akin to previous studies 10,20,21,25,33,34,36‐40 . In fact, most earlier publications on hTERC expression have focussed on the frequency of hTERC positivity in various cytology and/or histology categories, deriving their cut‐offs from percentage of hTERC‐expressing cells in normal/ negative samples.…”
Section: Discussionsupporting
confidence: 73%
“…The proportion of cases with hTERC gene overexpression showed a significant increment with progressively increasing cytological and histological abnormalities, findings akin to previous studies 10,20,21,25,33,34,36‐40 . In fact, most earlier publications on hTERC expression have focussed on the frequency of hTERC positivity in various cytology and/or histology categories, deriving their cut‐offs from percentage of hTERC‐expressing cells in normal/ negative samples.…”
Section: Discussionsupporting
confidence: 73%
“…CCND1 belongs to the highly conserved cyclin family and plays a key role in the cell cycle transition from G1 phase to S phase transition ( 59 ). MYC is a proto-oncogene that encodes a nuclear phosphoprotein and is involved in cell proliferation, the cell cycle, and apoptosis ( 60 ). However, there have been no reports regarding the role of the four genes in quercetin treatment of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of normal cell proliferation, the expression of c-Myc is strictly controlled, but in malignancies of different histogenetic origins, the increased c-Myc expression is often observed. In cervical cancer, recent reports have indicated that the c-Myc expression increases with increasing severity of histological diagnosis (Heng et al, 2018;Ji et al, 2018); these results emphasize the potential function of c-Myc as an indicator in cervical cancer (Li et al, 2014;Gao et al, 2015;. In this study, the expression of the proto-oncogene c-Myc was notably decreased in a dose-and time-dependent manner at both the mRNA and protein levels in two human cervical cancer cell lines (CaSki and C33A) after PD treatment.…”
Section: Discussionmentioning
confidence: 99%